Charlie Bone and the Red Knight - Nimmo, Jenny (Nimmo, Jenny. Children of the red king, 2010)
Charlie and the Children of the Red King must call upon all of their strength to defeat the darkness and finally learn the fate of Charlie's family, the evil intentions of the Bloors, what has become of Septimus Bloor's will, and the destiny of the Red King's heirs.